Successfully reported this slideshow.
We use your LinkedIn profile and activity data to personalize ads and to show you more relevant ads. You can change your ad preferences anytime.

Fourier integral of Fourier series

1,031 views

Published on

Fourier Integral of Advanced engineering Mathematics.

Published in: Engineering
  • Login to see the comments

Fourier integral of Fourier series

  1. 1. Gandhinagar Institute ofTechnology Fourier Integral Mehta Chintan B. D1-14 3rd SEM. Mech. D Guided By:- Prof. M. S. Suthar Advanced Engineering Mathematics (2130002)
  2. 2. Fourier Series β€’ As we know that the fourier series of function f(x) in any interval (-l, l) is given by: β€’ 𝑓 π‘₯ = π‘Ž0 + 𝑛=1 ∞ π‘Ž 𝑛 cos π‘›πœ‹π‘₯ 𝐿 + 𝑏 𝑛 sin π‘›πœ‹π‘₯ 𝐿 β€’ Where:- β€’ π‘Ž0 = 1 2𝑙 βˆ’π‘™ 𝑙 𝑓 𝑑 𝑑𝑑 β€’ π‘Ž 𝑛= 1 𝑙 βˆ’π‘™ 𝑙 𝑓 𝑑 π‘π‘œπ‘  π‘›πœ‹π‘‘ 𝑙 𝑑𝑑 β€’ 𝑏 𝑛= 1 𝑙 βˆ’π‘™ 𝑙 𝑓 𝑑 𝑠𝑖𝑛 π‘›πœ‹π‘‘ 𝑙 𝑑𝑑
  3. 3. Fourier Integral β€’ Let f(x) be a function which is piecewise continuous in every finite interval in (βˆ’βˆž, ∞) and absolute integral in (βˆ’βˆž, ∞). β€’ Then 𝑓 π‘₯ = 1 πœ‹ 0 ∞ ( βˆ’βˆž ∞ 𝑓 𝑑 π‘π‘œπ‘ πœ” 𝑑 βˆ’ π‘₯ 𝑑𝑑)π‘‘πœ” β€’ Where : β€’ πœ” = π‘›πœ‹ 𝑙 β€’ 𝑙 β†’ ∞
  4. 4. Proof of Fourier Integral 𝑓 π‘₯ = π‘Ž0 + 𝑛=1 ∞ π‘Ž 𝑛 cos π‘›πœ‹π‘₯ 𝐿 + 𝑏 𝑛 sin π‘›πœ‹π‘₯ 𝐿 𝑓 π‘₯ = 1 2𝑙 βˆ’π‘™ 𝑙 𝑓 𝑑 𝑑𝑑 + 𝑛=1 ∞ 1 𝑙 βˆ’π‘™ 𝑙 𝑓 𝑑 π‘π‘œπ‘  π‘›πœ‹π‘‘ 𝑙 π‘π‘œπ‘  π‘›πœ‹π‘₯ 𝑙 𝑑𝑑 + 𝑛=1 ∞ 1 𝑙 βˆ’π‘™ 𝑙 𝑓 𝑑 𝑠𝑖𝑛 π‘›πœ‹π‘‘ 𝑙 𝑠𝑖𝑛 π‘›πœ‹π‘₯ 𝑙 𝑑𝑑 = 1 2𝑙 βˆ’π‘™ 𝑙 𝑓 𝑑 𝑑𝑑 + 𝑛=1 ∞ 1 𝑙 βˆ’π‘™ 𝑙 𝑓(𝑑) π‘π‘œπ‘  π‘›πœ‹π‘‘ 𝑙 π‘π‘œπ‘  π‘›πœ‹π‘₯ 𝑙 𝑑𝑑 + 𝑠𝑖𝑛 π‘›πœ‹π‘‘ 𝑙 𝑠𝑖𝑛 π‘›πœ‹π‘₯ 𝑙 𝑑𝑑 = 1 2𝑙 βˆ’π‘™ 𝑙 𝑓 𝑑 𝑑𝑑 + 1 𝑙 𝑛=1 ∞ βˆ’π‘™ 𝑙 𝑓 𝑑 π‘π‘œπ‘  π‘›πœ‹ 𝑙 𝑑 βˆ’ π‘₯ 𝑑𝑑
  5. 5. β€’ Putting πœ” 𝑛 = π‘›πœ‹ 𝑙 and βˆ†πœ” 𝑛 = πœ” 𝑛+1 βˆ’ πœ” 𝑛 = 𝑛 + 1 πœ‹ 𝑙 βˆ’ πœ‹ 𝑙 = πœ‹ 𝑙 so βˆ†πœ” 𝑛 πœ‹ = 1 𝑙 𝑓 π‘₯ = 1 2𝑙 βˆ’π‘™ 𝑙 𝑓 𝑑 𝑑𝑑 + βˆ†πœ” 𝑛 πœ‹ 𝑛=1 ∞ βˆ’π‘™ 𝑙 𝑓 𝑑 π‘π‘œπ‘ πœ” 𝑛 𝑑 βˆ’ π‘₯ 𝑑𝑑 β€’ As 𝑙 β†’ ∞, 1 𝑙 = 0 and βˆ†πœ” 𝑛 = πœ‹ 𝑙 β†’ 0, the infinite series in above equation becomes an integral from 0 π‘‘π‘œ ∞ 𝑓 π‘₯ = 1 πœ‹ 0 ∞ βˆ’βˆž ∞ 𝑓 𝑑 cos πœ” 𝑑 βˆ’ π‘₯ 𝑑𝑑 π‘‘πœ” β€’ Now expanding π‘π‘œπ‘ πœ”(𝑑 βˆ’ π‘₯) in above equation.
  6. 6. 𝑓 π‘₯ = 1 πœ‹ 0 ∞ ( βˆ’βˆž ∞ 𝑓 𝑑 π‘π‘œπ‘ πœ”π‘‘ π‘π‘œπ‘ πœ”π‘₯ + π‘ π‘–π‘›πœ”π‘‘ π‘ π‘–π‘›πœ”π‘₯) π‘‘πœ” = 1 πœ‹ 0 ∞ βˆ’βˆž ∞ 𝑓 𝑑 π‘π‘œπ‘ πœ”π‘‘π‘‘π‘‘ π‘π‘œπ‘ πœ”π‘₯π‘‘πœ” + 1 πœ‹ 0 ∞ βˆ’βˆž ∞ 𝑓 𝑑 π‘ π‘–π‘›πœ”π‘‘π‘‘π‘‘ π‘ π‘–π‘›πœ”π‘₯π‘‘πœ” = 0 ∞ 𝐴 πœ” π‘π‘œπ‘ πœ”π‘₯π‘‘πœ” + 0 ∞ 𝐡 πœ” π‘ π‘–π‘›πœ”π‘₯π‘‘πœ” β€’ Where: β€’ 𝐴 πœ” = 1 πœ‹ βˆ’βˆž ∞ 𝑓 𝑑 π‘π‘œπ‘ πœ”π‘‘π‘‘π‘‘ β€’ B πœ” = 1 πœ‹ βˆ’βˆž ∞ 𝑓 𝑑 π‘ π‘–π‘›πœ”π‘‘π‘‘π‘‘
  7. 7. Fourier cosine integrals β€’ When 𝑓(π‘₯) is an even function: β€’ 𝐴 πœ” = 2 πœ‹ 0 ∞ 𝑓 𝑑 π‘π‘œπ‘ πœ”π‘‘π‘‘π‘‘ and B πœ” = 0 β€’ So the fourier integrals of an even function is given by: β€’ 𝑓(π‘₯) = 0 ∞ 𝐴 πœ” π‘π‘œπ‘ πœ”π‘₯π‘‘πœ”
  8. 8. Fourier sin integral β€’ When 𝑓(π‘₯) is an odd function: β€’ 𝐴 πœ” = 0 and B πœ” = 2 πœ‹ 0 ∞ 𝑓 𝑑 π‘ π‘–π‘›πœ”π‘‘π‘‘π‘‘ β€’ So the fourier integral of odd function is given by: β€’ 𝑓(π‘₯) = 0 ∞ 𝐡 πœ” π‘ π‘–π‘›πœ”π‘₯π‘‘πœ”
  9. 9. Fourier cosine sum β€’ Find the fourier cosine integral of 𝒇 𝒙 = π’†βˆ’π’Œπ’™, where 𝒙 > 𝟎, π’Œ > 𝟎 hence show that 𝟎 ∞ π’„π’π’”πŽπ’™ 𝒂 𝟐+𝝎 𝟐 π’…πŽ = 𝝅 πŸπ’‚ π’†βˆ’π’‚π’™ οƒ˜The fourier cosine integral of 𝑓 π‘₯ is given by: 𝑓 π‘₯ = 0 ∞ 𝐴 πœ” π‘π‘œπ‘ πœ”π‘₯π‘‘πœ” 𝐴 πœ” = 2 πœ‹ 0 ∞ 𝑓 𝑑 π‘π‘œπ‘ πœ”π‘‘π‘‘π‘‘ = 2 πœ‹ 0 ∞ π‘’βˆ’π‘˜π‘‘ π‘π‘œπ‘ πœ”π‘‘π‘‘π‘‘ = 2 πœ‹ π‘’βˆ’π‘˜π‘‘ π‘˜2 + πœ”2 (βˆ’π‘˜π‘π‘œπ‘ πœ”π‘‘ + πœ”π‘ π‘–π‘›πœ”π‘‘ (π‘“π‘Ÿπ‘œπ‘š 0 π‘‘π‘œβˆž) = 2 πœ‹ ( π‘Ž π‘Ž2 + πœ”2)
  10. 10. β€’ Hence: 𝑓 π‘₯ = 2π‘Ž πœ‹ 0 ∞ 1 π‘Ž2 + πœ”2 π‘π‘œπ‘ πœ”π‘₯π‘‘πœ” 0 ∞ π‘π‘œπ‘ πœ”π‘₯ π‘Ž2 + πœ”2 π‘‘πœ” = πœ‹ 2π‘Ž 𝑓(π‘₯) = πœ‹ 2π‘Ž π‘’βˆ’π‘Žπ‘₯ (x > 0, π‘Ž > 0)
  11. 11. Fourier sine integral sum β€’ Find the sine integral of 𝑓 π‘₯ = π‘’βˆ’π‘π‘₯ , hence show that πœ‹ 2 π‘’βˆ’π‘π‘₯ = 0 ∞ πœ”π‘ π‘–π‘›πœ”π‘₯ 𝑏2+πœ”2 π‘‘πœ” οƒ˜The fourier sine integral of 𝑓 π‘₯ is given by: 𝑓(π‘₯) = 0 ∞ 𝐡 πœ” π‘ π‘–π‘›πœ”π‘₯π‘‘πœ”
  12. 12. 𝐡 πœ” = 2 πœ‹ 0 ∞ 𝑓 𝑑 π‘ π‘–π‘›πœ”π‘‘π‘‘π‘‘ = 2 πœ‹ 0 ∞ π‘’βˆ’πœ”π‘‘ π‘ π‘–π‘›πœ”π‘‘π‘‘π‘‘ = 2 πœ‹ π‘’βˆ’π‘π‘‘ 𝑏2 + πœ”2 (βˆ’π‘π‘ π‘–π‘›πœ”π‘‘ βˆ’ πœ”π‘π‘œπ‘ πœ”π‘‘) (π‘“π‘Ÿπ‘œπ‘š 0 π‘‘π‘œ ∞) = 2 πœ‹ ( πœ” 𝑏2 + πœ”2 )
  13. 13. β€’ Hence: 𝑓 π‘₯ = 2 πœ‹ 0 ∞ πœ”π‘ π‘–π‘›πœ”π‘₯ 𝑏2 + πœ”2 π‘‘πœ” 0 ∞ πœ”π‘ π‘–π‘›πœ”π‘₯ 𝑏2 + πœ”2 π‘‘πœ” = πœ‹ 2 𝑓 π‘₯ 0 ∞ πœ”π‘ π‘–π‘›πœ”π‘₯ 𝑏2 + πœ”2 π‘‘πœ” = πœ‹ 2 π‘’βˆ’π‘π‘₯(x > 0, 𝑏 > 0)
  14. 14. References β€’ Advanced engineering mathematics ofTATA McGraw Hill β€’ https://www.wikipedia.org>wiki>fourier_integral β€’ https://mathonline.wikidot.com
  15. 15. ThankYou

Γ—